(untitled) (Journal of the College of Basic Education, 2025)
This study involves evaluation of ambient air quality at Al-Basra province (south of Iraq). Sixteen different areas were chosen for monitoring of airborne contaminants during the period from December 2022 to January 2023. Air pollutants were monitored by a handheld gas analyzer for NOX, SOx, CO2, HC and CO, while portable dust sampler device was used to measure total suspended particles (TSP). The results of the sampling and analysis of the air pollutants show that the total suspended particulates (TSP) values ranged from 172-322 µg/m3, CO ranged from 3.12-11.32 ppm, CO2 ranged from 232-411 ppm, SOx ranged from 0.79-4.05 ppm, NOx ranged from 0.76-2.61 ppm and HC ranged from 0.01-0.97 ppm. The results of human health risk assessment using Hazard Quotient (HQ) approach show high risk due to relatively elevated concentrations of airborne pollutants.